Evaluation of Serum and Plasma Interleukin-6 Levels in Obstructive Sleep Apnea Syndrome: A Meta-Analysis and Meta-Regression - Imani, Mohammad Moslem; Sadeghi, Masoud; Khazaie, Habibolah; Emami, Mostafa; Sadeghi Bahmani, Dena; Brand, Serge (Frontiers in Immunology, 2020)
Obstructive sleep apnea syndrome (OSAS) is considered a low-grade chronic inflammatory disease. Interleuking-6 (IL-6) is one of the most significant inflammatory markers and an excellent proxy for the inflammatory/immune system. The present meta-analysis and meta-regression aimed at comparing plasma and serum levels of IL-6 between individuals (children and adults) with OSAS and healthy controls. Four databases, PubMed/Medline, Scopus, Cochrane Library, and Web of Science, were comprehensively searched to retrieve articles published up to December, 2019, with no further restrictions. RevMan 5.3 software was used to calculate the crude mean difference (MD) and 95% confidence interval (CI). The results of funnel plots and meta-regression were analyzed by the CMA 2.0 software. Sixty-five studies (57 with adults; 8 with children) were included in the present meta-analysis. For adults, 37 studies reported significantly higher serum IL-6 levels and 20 reported significantly higher plasma IL-6 levels for those with OSAS than for healthy controls (pooled MD of 2.89 pg/mL [P<0.00001] and pooled MD of 2.89 pg/mL [P<0.00001], respectively). The pooled analysis of serum and plasma IL-6 levels in children with OSAS compared with controls revealed that only the MD of plasma IL-6 levels was significant (MD = 0.69 pg/mL, P<0.00001). Results of the meta-regression showed that greater age was associated with higher serum IL-6 levels. Egger’s test revealed a publication bias across the studies for serum and plasma IL-6 levels (P=0.00044 and P=0.01445, respectively). In summary, the meta-analysis and meta-regression confirmed that, compared to healthy controls, individuals with OSAS (children and adults) had higher serum/plasma IL-6 levels.